Hubungan Korelasional Antara Kompetensi Manajerial dan Sistem Kontrol Internal Terhadap Kinerja Keuangan Pemerintah Provinsi Gorontalo - Junus, Onong; Abdullah, Julie (Universitas Gorontalo, 2018)
This study aimed to analyze the correlation relationship between managerial competence and control systems to the financial performance of Gorontalo Provincial Government. A total of 648 employees of the finance department and samples taken as many as 247 respondents by formula Slovin. Data from the questionnaires were analyzed using Structural Equation Model using AMOS aid 18.The results found that the internal control system directly and not significant positive effect on financial performance. Means the internal control system has been implemented, but has not been able to achieve results that match the input, process, output, outcome, benefit and impact as an assessment of the organization's financial performance. Direct managerial competence dominant influence positive and significant impact on the financial performance of the organization. Means an employee-owned managerial competence are good and support the achievement of the work in the field of appropriate financial inputs, processes, outputs, outcomes, benefits and impact as well as the assessment of financial performance to the principles of management in the financial sector.